A Flexible Mouse-On-Mouse Immunohistochemical Staining Technique Adaptable to Biotin-Free Reagents, Immunofluorescence, and Multiple Antibody Staining. (March 2014) - Goodpaster, Tracy; Randolph-Habecker, Julie
Immunohistochemistry on mouse tissue utilizing mouse monoclonal antibodies presents a challenge. Secondary antibodies directed against the mouse monoclonal primary antibody of interest will also detect endogenous mouse immunoglobulin in the tissue. This can lead to significant spurious staining. Therefore, a "mouse-on-mouse" staining strategy is needed to yield credible data. This paper presents a method that is easy to use and highly flexible to accommodate both an avidin-biotin detection system as well as a biotin-free polymer detection system. The mouse primary antibody is first combined with an Fab fragment of an anti-mouse antibody in a tube and allowed sufficient time to form an antibody complex. Any non-complexed secondary antibody is bound up with mouse serum. The mixture is then applied to the tissue. The flexibility of this method is confirmed with the use of different anti-mouse antibodies followed by a variety of detection reagents. These techniques can be used for immunohistochemistry (IHC), immunofluorescence (IF), as well as staining with multiple primary antibodies. This method has also been adapted to other models, such as using human antibodies on human tissue and using multiple rabbit antibodies in dual immunofluorescence.